Recursive Variational Bayesian Inference to Simultaneous Registration and Fusion. (13th June 2016) - Zhu, Hao; Hu, Jinsong; Leung, Henry; Zhang, Bin
In this paper, we propose a novel simultaneous registration and fusion approach for tracking. This method is based on a recursive Variational Bayesian (RVB) algorithm, which is the online variant of the Variational Bayesian (VB) approach. Under the Bayesian framework, the states and parameters are recursively estimated. It is shown by simulation that the proposed RVB method has better estimation performance than the conventional approach.